Digital Marketing Strategy Applied to Expand MSME Market Reach in Rungkut Menjaga Village - Nabila Arinda Putri; Budi Prabowo (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
The development of science and technology (IPTEK) has made all aspects of human life turn to digitalization, including in the field of marketing. Digital marketing is a marketing technique that is carried out by utilizing electronic media or the internet, which can connect one person to another without time and distance limits. In this era, digital marketing is very important for MSME actors in expanding their market reach. Several MSME actors in Rungkut Menanggal Village have not used digital marketing due to a lack of knowledge and understanding of digital marketing. The purpose of this activity is to help solve the problems faced by MSMEs in the field of marketing and find and develop digital marketing strategies to expand the market reach of MSMEs. With this community service, MSMEs in Rungkut Menanggal Village can expand market reach through the dissemination of digital marketing strategies so that they are expected to increase sales of their products.